Onychomycosis in Students: An Overview of Nail Care Practices and Personal Hygiene - Lisa Savitri; Kharisul Ihsan; Rochmad Krissanjaya; Elfred Rinaldo Kasimo; Novirma Yanti; Mochamad Hanif Hilmi (Biology, Medicine, & Natural Product Chemistry, 2025)
Onychomycosis is a common nail disorder caused by dermatophytes, yeasts, and non-dermatophyte molds, with increasing prevalence among young adults. Poor nail care and personal hygiene habits are essential predisposing factors that contribute to infection. Despite its clinical relevance, data on onychomycosis in student populations remain limited. A cross-sectional study was conducted among 150 undergraduate students from the Faculty of Health Sciences, aged 18–25 years. Nail specimens were collected from individuals presenting with suspected onychomycosis. Direct microscopy was performed using a 20% potassium hydroxide (KOH) preparation, and samples were cultured on Sabouraud Dextrose Agar supplemented with chloramphenicol and cycloheximide. Fungal isolates were identified based on macroscopic and microscopic characteristics. Sociodemographic data, nail care habits, and hygiene practices were collected through structured questionnaires. Data were analyzed descriptively, and associations were assessed using chi-square tests. Onychomycosis was confirmed in 27 students (18%). Dermatophytes were the most frequent isolates, with Trichophyton rubrum (9%) and T. mentagrophytes (5%) predominating, followed by Candida albicans (3%) and Aspergillus spp. (1%). Risk factors significantly associated with infection included irregular nail trimming (p = 0.01), sharing of nail clippers (p = 0.03), and prolonged use of closed footwear (p = 0.02). No significant associations were observed with gender or age. Onychomycosis is prevalent among university students, with dermatophytes as the leading causative agents. Inadequate nail care and poor hygiene practices play a critical role in the occurrence of diseases. Health education and preventive interventions should be prioritized to reduce infection rates in young adults. Further studies employing molecular methods are recommended to refine species identification and improve epidemiological insights.